UV-curable nano-silver containing polyurethane based organic-inorganic hybrid coatings - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2013)
The preparation of nano-silver containing polyurethane based UV-curable organic-inorganic hybrid coatings that have antibacterial activity is presented in this paper. Trimethoxysilane end-capped bis[(4-beta-hydroxyethoxy)phenyl] methyl phosphine oxide urethane was synthesized as a coupling agent and used to improve the compatibility between the organic and inorganic phases of the hybrid coating. Due to its strong antibacterial activity, silver nanoparticles were prepared and added to the nanocomposite formulations. The relationships between the amount of coupling agent and the final coating properties were investigated. The hybrid coatings presented good thermal stability. Tests for abrasion, hardness, gloss, and adhesion of the coatings were also performed. The morphological investigation was performed by SEM to determine the size of the silver nanoparticles. The nano-silver containing coatings exhibited good antibacterial activity against E. coli and S. aureus. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: UV-curable; Nanocomposite coatings; Sol-gel; Silver nanoparticle; Antimicrobial; COLLOIDAL SILICA; NANOPARTICLES; PPG